ByzRev 08.2026.034: Gabriel Radle, Marriage in Byzantium: Christian Liturgical Rites from Betrothal to Consummation. Cambridge University Press 2024 - Afentoulidou, Eirini (The Byzantine Review, 2026)
Gabriel Radle, Marriage in Byzantium. Christian Liturgical Rites from Betrothal to Consummation. Cambridge University Press 2024. 468 pp. – ISBN 978-1-009-46956-2